Concept Mapping and Mind Mapping to Lift the Thinking Skills of Chemical Engineering Students - Joao, Isabel M.; Silva, João M. (International Journal of Engineering Pedagogy (iJEP), 2014)
Chemical product and process design teaching is facing challenges due to the major changes occurred in the last decades in the chemical industry. The emergence of products as a focus for chemical engineers implies changes in what chemical engineers do. It is important to prepare students for the more diverse, flexible roles they are expected to perform in industry and nowadays it is requisite that chemical engineers participate in the whole process from conception to manufacture. This paper addresses the activity of ideas generation, a very important step in product and process design procedure, and explores the role of concept maps and mind maps along with the discussion of the main features of the methods used to map and structure the ideas. The main goal of this paper is to present the methods within the context of product and process design teaching and learning showing the potentialities of the methods as graphical representations, in the ideas generation step in order to allow free-flowing thoughts. An illustration of the maps performed by chemical and biological engineering master students within the product and process design curricular unit is presented along with the main conclusions. This type of maps is promising in order to allow chemical and biological engineering students gradually lift their skills.